Critical Discourse Analysis of Anies Baswedan’s 2024 Indonesian Presidential Campaign Strategies - Eky Erlanda Edel; Wawan Gunawan; Mahardika Zifana; Adam Muhammad Nur (RETORIKA: Jurnal Ilmu Bahasa, 2025)
How can campaign strategies impact a political election? This qualitative descriptive research focuses on Anies Baswedan's political campaign strategies for the 2024 Presidential Election in Indonesia from six selected topics of Baswedan in Q & A session. The data was taken from his “Desak Anies” campaign program conducted in Semarang and uploaded by Metro TV to its official YouTube channel a week before election day. From those topics, the researcher chose nineteen highlighted quotations to be analyzed by using Van Dijk’s Framework (1991, 1995, 2006) and Yule (2010) focus on the macro-levels (the general meaning), superstructure (introduction, body, and closing), and micro-levels of political discourse strategies, which are implication, presupposition, hyperbole, compassion move, negative comparison, blaming the victim, contrast and division, actor description, number game, metaphor, repetition, and pronouns. The result shows that Baswedan's most used strategy is the Actor Description, which is taken from six different topics. Using systematic answers like introduction, body, and closing was typical of Baswedan answers. It can be said that using those complex sentences is the way to ensure that his audience completely understands his ideology, qualities, and achievements as a politician, leader, and human being. Furthermore, the data shows that Baswedan political campaign strategies focus on understanding the political landscape, competitor analysis, and strategy development, developing a clear and relatable campaign message, effective use of digital tools and social media, field organizing and voter contact, building community support and visibility, handling misinformation and negative campaigning, and get out of the vote (GOTV) strategies.